Omega-3 polyunsaturated fatty acids in cardiac surgery patients: An updated systematic review and meta-analysis. Issue 3 (June 2017) - Langlois, Pascal L.; Hardy, Gil; Manzanares, William
Summary: Background: Omega-3 polyunsaturated fatty acids (ω-3 PUFA) supplementation is an attractive therapeutic option for patients undergoing open-heart surgery due to their anti-inflammatory and anti-arrhythmic properties. Several randomized controlled trials (RCT) have found contradictory results for perioperative ω-3 PUFA administration. Therefore, we conducted an updated systematic review and meta-analysis evaluating the effects of perioperative ω-3 PUFA on some clinically important outcomes for cardiac surgery. Methods: A systematic literature search was conducted to find RCT evaluating clinical outcomes after ω-3 PUFA therapy in adult patients undergoing cardiac surgery. Intensive care unit (ICU) length of stay (LOS) was the primary outcome; secondary outcomes were hospital LOS, postoperative atrial fibrillation (POAF), mortality and duration of mechanical ventilation (MV). Predefined subgroup analysis and sensibility analysis were performed. Results: A total of 19 RCT including 4335 patients met inclusion criteria. No effect of ω-3 PUFA on ICU LOS was found ( weighted mean difference WMD −2.95, 95% confidence interval, CI −10.28 to 4.39, P = 0.43). However, ω-3 PUFA reduced hospital LOS (WMD −1.37, 95% CI −2.41 to −0.33; P = 0.010) and POAF incidence ( Odds Ratio OR = 0.78, 95% CI 0.68 to 0.90; P = 0.004). No effects were found on mortality or MV duration. Heterogeneity remained in subgroup analysis and we found a significant POAF reduction when ω-3 PUFA doses were administered to patients exposed to extra-corporeal circulation. Oral/enteral administration seemed to further reduce POAF. Conclusions: In patients undergoing cardiac surgery, ω-3 PUFA supplementation by oral/enteral and parenteral route reduces hospital LOS and POAF. Nonetheless considerable clinical and statistical heterogeneity weaken our findings.